The multifaceted biology of lncR-Meg3 in cardio-cerebrovascular diseases - Li, Jing; Liu, Wenxiu; Peng, Fu; Cao, Xiaoyu; Xie, Xiaofang; Peng, Cheng (Frontiers in Genetics, 2023)
Cardio-cerebrovascular disease, related to high mortality and morbidity worldwide, is a type of cardiovascular or cerebrovascular dysfunction involved in various processes. Therefore, it is imperative to conduct additional research into the pathogenesis and new therapeutic targets of cardiovascular and cerebrovascular disorders. Long non-coding RNAs (lncRNAs) have multiple functions and are involved in nearly all cellular biological processes, including translation, transcription, signal transduction, and cell cycle control. LncR-Meg3 is one of them and is becoming increasingly popular. By binding proteins or directly or competitively binding miRNAs, LncR-Meg3 is involved in apoptosis, inflammation, oxidative stress, endoplasmic reticulum stress, epithelial-mesenchymal transition, and other processes. Recent research has shown that LncR-Meg3 is associated with acute myocardial infarction and can be used to diagnose this condition. This article examines the current state of knowledge regarding the expression and regulatory function of LncR-Meg3 in relation to cardiovascular and cerebrovascular diseases. The abnormal expression of LncR-Meg3 can influence neuronal cell death, inflammation, apoptosis, smooth muscle cell proliferation, etc., thereby aggravating or promoting the disease. In addition, we review the bioactive components that target lncR-Meg3 and propose some potential delivery vectors. A comprehensive and in-depth analysis of LncR-Meg3’s role in cardiovascular disease suggests that targeting LncR-Meg3 may be an alternative therapy in the near future, providing new options for slowing the progression of cardiovascular disease.